Transition Readiness in Adolescents With Juvenile Idiopathic Arthritis and Childhood‐Onset Systemic Lupus Erythematosus. Issue 4 (12th March 2021) - McColl, Jeanine; Semalulu, Teresa; Beattie, Karen A.; Alam, Arzoo; Thomas, Steffy; Herrington, Julie; Gorter, Jan Willem; Cellucci, Tania; Garner, Stephanie; Heale, Liane; Matsos, Mark; Batthish, Michelle
Abstract : Objective: The transition from pediatric to adult rheumatology care represents a particularly vulnerable time for patients with juvenile idiopathic arthritis (JIA) and childhood‐onset systemic lupus erythematosus (cSLE). Improving self‐management skills is important in optimizing health care transition. The study's objectives were to 1) examine variability in transition readiness of adolescents and young adults within and between different ages, sexes, and disease types; 2) determine the association between age and transition readiness; and 3) identify specific challenges to transition readiness for adolescents. Methods: Over 1 year, patients 14 to 20 years of age with JIA or cSLE were recruited from pediatric transition and young adult clinics at a single academic institution. Participants completed the 14‐item Transition‐Q at a single time point. Total scores range from 0 to 100; higher scores indicate greater health care self‐management skills as a proxy for transition readiness. Descriptive statistics summarized patient characteristics and Transition‐Q scores for the population. Regression analyses determined the association between age, sex, and disease type and Transition‐Q score. Results: Among 70 participants, 61 had JIA and 9 cSLE (mean disease duration 4.6 years). The mean (SD) total Transition‐Q score was 59.8 (14.9). Age was significantly associated with Transition‐Q score (standardized β = 0.372l P = 0.002). The most commonly reported challenges were seeing the physician alone (without parents), making one's own appointments, picking up prescriptions, and independent transportation for appointments. Conclusion: Transition readiness appears to increase with patient age. There is significant variability in Transition‐Q scores between patients of the same age, suggesting that an individualized approach to improving self‐management skills is necessary.